2019
DOI: 10.3390/nu11040917
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Docosahexaenoic Acid (DHA) and Eicosapentaenoic Acid (EPA) Operate by Different Mechanisms to Modulate Hepatic Steatosis and Hyperinsulemia in fa/fa Zucker Rats

Abstract: Hepatic steatosis, an early stage of non-alcoholic fatty liver disease, is commonly present in obesity and type 2 diabetes, and is associated with reduced hepatic omega-3 polyunsaturated fatty acid (n3-PUFA) status that impacts on the anti-inflammatory and insulin sensitizing functions of n3-PUFA. Our objective was to directly compare plant- and marine-based n3-PUFA (α-linoleic acid (ALA)), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA)) for their effects on hepatic steatosis, markers of hepatic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
5
20
1
1
Order By: Relevance
“…DESI-IMS is a recently developed technique that can be used to analyze the spatial distribution and identification of biomolecules, metabolites, and drugs [28]. Moreover, lipids and FFAs are easily ionized in DESI-IMS, and their metabolism lies at the core of many diseases, including dementia and cancer [4,23,25,32]. Seven molecular ions of FFAs were detected from the mass spectra of DESI-IMS, acquired in negative ion mode from brain slices of SAMP8 mice.…”
Section: Discussionmentioning
confidence: 99%
“…DESI-IMS is a recently developed technique that can be used to analyze the spatial distribution and identification of biomolecules, metabolites, and drugs [28]. Moreover, lipids and FFAs are easily ionized in DESI-IMS, and their metabolism lies at the core of many diseases, including dementia and cancer [4,23,25,32]. Seven molecular ions of FFAs were detected from the mass spectra of DESI-IMS, acquired in negative ion mode from brain slices of SAMP8 mice.…”
Section: Discussionmentioning
confidence: 99%
“…analysis of Oil Red staining. Many studies confirmed the peculiar ability of the main nutrients of our extracts, that are mixed with single bioactive compounds, to reduce hepatic steatosis: silymarin was proved to attenuate insulin resistance and hepatic steatosis after 3 months of treatment [60]; PIVENS trials demonstrated the therapeutic activity of tocopherol, however limited in its administration due to safety concerns [7]; DHA was reported to be protective in combination with the other polyunsaturated fatty acid EPA [16]; choline-deficiency and its metabolism by gut microbiota were associated with hepatic steatosis development [61]; chlorogenic acid injections reduced lipid accumulation in the liver of HFD fed mice [51]; parthenolide was not directly reported to lower hepatic steatosis, but it was documented to reduce liver triacylglycerol levels [58].…”
Section: Discussionmentioning
confidence: 62%
“…Silymarin is the principal component of the medicinal plant Silybum marianum : in a juvenile model of NASH, its supplementation to the diet ameliorated glucose and lipid profiles, reduced fibrosis, inflammation and oxidation [ 15 ]. Docosahexaenoic acid (DHA) is an omega-3 fatty acid deriving from marine sources; according with previous evidence, it is low-concentrated in the blood and liver of NASH patients and its supplementation in pre-clinical and clinical studies inhibited the progression of hepatic steatosis and showed hypotriglyceridemic properties, thus ameliorating nutritional NAFLD [ 16 , 17 ]. Choline is an indispensable nutrient whose metabolism is regulated by the liver and whose dietary deficiency paves the way to fatty liver and its more aggressive declinations: European Food Safety Agency (EFSA) defined it as the food ingredient necessary for a “healthy functioning liver” [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies revealed that dietary supplementation of ω-3 PUFA is potent in reducing hepatic steatosis, improving insulin resistance and ameliorating inflammation in NAFLD-affected individuals [77]. In fact, dietary docosahexaenoic acid (DHA) was the most effective PUFA in preventing the progression of hepatic fat accumulation and reducing fasting hyperinsulinemia in NAFLD patients and fa/fa Zucker diabetic rats with hepatic steatosis and diabetes [78,79]. This area of research is still very limited; however, only hypocaloric diets with either low-fat or low-carbohydrate energy deficits attenuated T2D development in patients with NAFLD [80,81].…”
Section: T2d Develops When Hepatic Autoregulation Is Lost-a Matter Ofmentioning
confidence: 99%